Method and equipment for improving plasticizing rate of ETFE (Ethylene Tetra Fluoro Ethylene)
By improving the screw structure and installing dispersed hybrid components, the problem of the ETFE plasticization process being affected by various factors is solved, the plasticization rate and product quality are improved, and the output is improved.
Patent Information
- Application Number
- CN202411674107.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-14
AI Technical Summary
The plasticization process of ETFE is easily affected by various factors such as the properties of raw materials, equipment structure and processing conditions, resulting in a low plasticization rate, which in turn affects the quality and performance of the final product.
By selecting ETFE raw materials with uniform molecular weight distribution and suitable melt index, and improving the screw structure based on solid conveying theory, transient melting theory and melt conveying theory, adjusting the screw length and diameter ratio, optimizing the screw groove depth and compression ratio, and installing dispersed hybrid components to improve the plasticization rate.
It improves the plasticization rate of ETFE, improves the quality and performance of the final product, and can increase the output by 30% to 40%, while avoiding local overheating and uneven molecular distribution.
Smart Images

Figure CN119610604A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic processing, and in particular to a method and equipment for improving the plasticization rate of ETFE. Background Art
[0002] The plasticization rate of a material refers to the speed and degree to which a plastic changes from a solid state to a molten state during processing. The plasticization rate is usually related to the heating temperature, screw design, screw speed, type of plastic, and cooling system. Ethylene-tetrafluoroethylene alternating copolymer (ETFE), with a structural formula of [CF2-CF2-CH2-CH2-], is referred to as F40 in industry. It is a crystalline polymer with low shear sensitivity and a wide processing temperature window. It is suitable for various melt processing technologies and can be made into films by film pressing, extrusion, etc.
[0003] The quality of ETFE raw materials has a great influence on the extrusion plasticization rate. Relevant literature shows that the molar ratio of tetrafluoroethylene-based units and ethylene-based units in the ethylene / tetrafluoroethylene copolymer used for extrusion molding equipment to make ETFE film is: 80 / 20~40 / 60. The unit ratio of the third monomer other than ethylene and tetrafluoroethylene should account for 0.01~20mol% of the total units of the copolymer. Chain transfer agents are added during the synthesis of ETFE resin to improve the molecular weight distribution and increase its melt index, and other impurity elements will also be introduced at the same time. At present, a single-screw extruder is used to melt ETFE resin. The more advanced extrusion molding equipment for producing ETFE film is a five-stage single-screw extruder. Since the five-stage barrel is connected by a flange, there will be a certain temperature hysteresis when the heating rod is heated. ETFE is a thermoplastic resin, and its melting and flow are mainly controlled by temperature. The shear sensitivity of ETFE resin is not as obvious as other polymers. During processing, shear force can assist plasticization, but it is not the dominant factor. The five-stage barrel has certain defects in the temperature control of ETFE resin processing.
[0004] In summary, in the prior art, the plasticization process of ETFE is easily affected by various factors such as the properties of raw materials, equipment structure and processing conditions, resulting in a low plasticization rate, which in turn affects the quality and performance of the final product. Summary of the invention
[0005] The object of the present invention is to provide a method and a device for improving the plasticization rate of ETFE, aiming to solve the technical problem in the prior art that the plasticization process of ETFE is easily affected by various factors such as raw material properties, equipment structure and processing conditions, resulting in a low plasticization rate, thereby affecting the quality and performance of the final product.
[0006] To achieve the above object, a method for improving the plasticizing rate of ETFE adopted in the present invention comprises the following steps:
[0007] Select ETFE raw materials with uniform molecular weight distribution, melt index of 10-20g / 10min, crystallinity of 65%-85%, and low content of foreign particles for use, and determine the physical and chemical properties of the processed materials to obtain specific processing performance parameters of the used ETFE materials;
[0008] The screw structure was improved based on the solid conveying theory, transient melting theory and melt conveying theory, the screw aspect ratio was adjusted to 30-40, the screw diameter D was adjusted to 65-110 mm, the effective length L of the screw was obtained based on the screw aspect ratio, and the screw groove depth and compression ratio were optimized to obtain the screw body;
[0009] The screw body is installed in a double-layer metal barrel, and a dispersing mixing element is installed in the double-layer metal barrel.
[0010] Among them, the molecular weight of the selected ETFE raw material is less than 1.26*10^ 6 , the impurity particle content is less than or equal to 2%.
[0011] Wherein, the material of the screw body is tungsten carbide or high nickel alloy.
[0012] The specific method for optimizing the screw groove depth is as follows: first, the groove depth H3 of the metering section is calculated by the following formula:
[0013]
[0014] Wherein, γ is the melt shear rate; D is the outer diameter of the screw; H3 is the groove depth of the metering section;
[0015] The optimal value of the metering section groove depth H3 is then calculated based on the following formula:
[0016]
[0017] Among them, K Q is the shape coefficient; L3 is the length of the metering section; D is the outer diameter of the screw; is the thread lead angle;
[0018] The compression ratio ε is optimized using the following formula:
[0019]
[0020] Wherein, D is the outer diameter of the screw; H1 is the groove depth of the feeding section; H3 is the groove depth of the metering section;
[0021] Based on the compression ratio and the groove depth of the metering section, the following formula is used to calculate the groove depth of the feeding section:
[0022]
[0023] Among them, ε is the geometric compression ratio; D is the outer diameter of the screw; H1 is the groove depth of the feeding section; H3 is the groove depth of the metering section.
[0024] Among them, when improving the screw structure, it is necessary to optimize its thread lead angle, which is calculated using the following formula:
[0025] S = πDtanΦ;
[0026] Wherein, S is the screw pitch; D is the screw outer diameter; is the thread lead angle;
[0027] The length of the metering section L3 is calculated using the following formula:
[0028]
[0029] Where Qp is the transport rate; is the lead angle of the thread; D is the outer diameter of the screw; H3 is the groove depth of the metering section; P is the pressure on the screw; η1 is the viscosity of ETFE; L3 is the length of the metering section.
[0030] Among them, when the screw structure is improved:
[0031] The inner diameter 1 of the chamfer of the push surface is calculated using the following formula:
[0032]
[0033] Among them, R1 is the inner diameter 1 of the chamfer of the pushing surface; H3 is the groove depth of the metering section;
[0034] The inner diameter 2 of the chamfer of the push surface is calculated using the following formula:
[0035] R2 = (2-3) R1;
[0036] Among them, R2 is the inner diameter 2 of the chamfer of the pushing surface; R1 is the inner diameter 1 of the chamfer of the pushing surface;
[0037] The normal width e of the screw edge is calculated using the following formula:
[0038] e=(0.08~0.12)D;
[0039] Where, e is the normal width of the screw fin; D is the outer diameter of the screw;
[0040] The axial width b of the screw flight is calculated using the following formula:
[0041]
[0042] Among them, b is the axial width of the screw flight; e is the normal width of the screw flight; φ is the thread lead angle.
[0043] The part of the double-layer metal barrel in contact with the compression section of the screw is designed as a grooved barrel and is staggered with the screw fins to form two transport grooves, a liquid phase groove and a solid phase groove.
[0044] Among them, the dispersed mixing element includes a through-groove mixing element and a convex-groove mixing element. The through-groove mixing element is installed 2D to 3D after the melting starting point and has a length of 2D to 3D. The convex-groove mixing element is installed at the end of the screw body and has a length of 1D to 2D.
[0045] The present invention also provides a plasticizing device for improving the plasticizing rate of ETFE, which is applied to the method for improving the plasticizing rate of ETFE as described above.
[0046] The invention comprises a double-layer metal barrel and a screw body, wherein the screw body is arranged in the double-layer metal barrel, the aspect ratio of the screw body is 30-40, and the diameter D is 65-110 mm.
[0047] The present invention discloses a method and device for improving the plasticization rate of ETFE. The present invention installs dispersed mixing elements in the melting zone and the melt conveying zone of the screw. The material passing through the melting zone enters the through groove before entering the conveying zone. The through groove is similar to a maze. The material moves in an S shape in the maze groove, so that the material is mixed more evenly. The fully melted liquid phase flows into the conveying zone from the barrel groove, and the solid-liquid mixed phase that is not fully melted continues to enter the through groove until it is completely melted and enters the conveying zone. The liquid phase entering the conveying zone is refluxed and stirred by the reverse force of the diverter plate and the extrusion, and the liquid phase is further plasticized. The convex groove mixing element is installed at the end of the screw body, and its length is between 1D and 2D. The viscous fluid resin is finally stirred and mixed before entering the die, so that the viscous fluid resin enters the die evenly, avoiding local overheating and uneven molecular distribution. In addition, the addition of mixing elements increases the outflow rate of the resin. Under the condition of ensuring that melt fracture does not occur, the output can be increased by 30% to 40%. In this way, the technical problem in the prior art that the plasticization process of ETFE is easily affected by various factors such as the properties of raw materials, equipment structure and processing conditions, resulting in a low plasticization rate, which in turn affects the quality and performance of the final product is solved.
[0048] Combined with the characteristics of the ETFE raw materials used, the screw is improved. First, with the help of solid conveying theory, the conveying efficiency of the solid conveying area is studied. The plasticizing method after adopting this method is:
[0049] ETFE resin is compacted after passing through the solid conveying area, and the air between the small gaps of the resin particles is also squeezed out to form a solid plug. The solid plug transitions into the melting zone, and the volume is changed by changing the screw width and screw depth. At this time, the integrity of the solid plug is destroyed and it is sheared into two or even more solid plugs. Extrusion friction occurs between the solid plugs to generate heat, and the resin begins to melt and form a molten film layer. In the transient melting theory, the moment the solid melts to form a molten film layer, it is taken away by the barrel, and the remaining solid begins to melt. The molten resin is taken away in time, and the exposed resin begins to melt, which can accelerate heat transfer, reduce resin decomposition, homogenize resin melting, and increase the resin plasticization rate. At the same time, a dispersed mixing element is installed in the melting zone, and the transient melting theory is used to guide the design of screw width and screw depth;
[0050] The resin that passes through the melting zone enters the melt conveying zone. This section uses POLYFLOW software to simulate the fluid mechanics process of the extrusion section and conducts the structural design of the screw melt conveying section. Through the simulation of geometric models and mathematical models, the boundary conditions and physical parameters are selected to conduct experimental design simulation results. The focus is on studying the influence of screw geometric parameters on the melt conveying rate, and the numerical simulation results are based on the melt conveying rate. By increasing the depth of the screw groove, the melt conveying efficiency at the extrusion metering end can be improved, and the unit consumption can be reduced. Based on this, the screw groove depth is optimized to further improve the plasticization rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0052] Attached Figure 1 It is the DSC curve diagram of the ETFE raw material used in the present invention.
[0053] Attached Figure 2 It is a schematic diagram of the relationship between the screw solid conveying angle of the present invention and the force M acting on the solid plug.
[0054] Attached Figure 3 It is a structural schematic diagram of the device for improving the plasticization rate of ETFE of the present invention.
[0055] Attached Figure 4 It is a structural schematic diagram of the threaded body of the present invention.
[0056] Attached Figure 5 It is a schematic diagram of the installation position of the through-channel mixing element.
[0057] 101-Double-layer metal barrel, 102-Screw body. DETAILED DESCRIPTION
[0058] Embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0059] Please refer to the attached Figure 1 ~Attached Figure 5 , including Figure 1 It is the DSC curve diagram of the ETFE raw material adopted by the present invention, attached Figure 2 Schematic diagram of the relationship between the screw solid conveying angle and the force M acting on the solid plug of the present invention, Figure 3 It is a structural schematic diagram of the equipment for improving the plasticization rate of ETFE of the present invention, Figure 4 Schematic diagram of the structure of the threaded body of the present invention, Figure 5 It is a schematic diagram of the installation position of the through-channel mixing element.
[0060] The present invention provides a method for improving the plasticization rate of ETFE, comprising the following steps:
[0061] S100, selecting ETFE raw materials with uniform molecular weight distribution, melt index of 10-20g / 10min, crystallinity of 65%-85%, and low impurity particle content for standby use, and determining the physical and chemical properties of the processed materials to obtain specific processing performance parameters of the used ETFE materials;
[0062] For this specific embodiment, the selected ETFE raw material molecular weight is less than 1.26*10^ 6 , the impurity particle content is less than or equal to 2%.
[0063] Please refer to the attached Figure 1 , according to the attached Figure 1 Determine the Tg (glass transition temperature, attached) of the ETFE material used Figure 1 a) and Tm (melting temperature, Figure 1 b), the temperature of the screw multi-stage heating should be controlled to be above the melting point of ETFE resin and below the decomposition temperature. The melting point of ETFE is 218℃~280℃, the processing temperature window is 280℃~340℃, and the critical shear rate is 200~3000s -1 In addition, a shear rate and viscosity relationship curve of ETFE resin is needed. There is no empirical relationship diagram for ETFE viscosity and shear rate at present, and it needs to be specifically measured for the ETFE raw materials used. The friction coefficient of plastic particles is between 0.25 and 0.4, and the friction coefficient of ETFE resin masterbatch is 0.3±0.05.
[0064] S200, based on the solid transport theory, transient melting theory and melt transport theory, the screw structure is improved, the screw aspect ratio is adjusted to 30-40, the screw diameter D is 65-110 mm, the effective length L of the screw is obtained based on the screw aspect ratio, and the screw groove depth and compression ratio are optimized to obtain the screw body 102;
[0065] In this specific embodiment, the material of the screw body 102 is tungsten carbide or high nickel alloy.
[0066] The specific method for optimizing the screw groove depth is as follows: first, the groove depth H3 of the metering section is calculated by the following formula:
[0067]
[0068] Wherein, γ is the melt shear rate; D is the outer diameter of the screw; H3 is the depth of the metering section groove;
[0069] The optimal value of the metering section groove depth H3 is then calculated based on the following formula:
[0070]
[0071] Among them, K Q is the shape coefficient; L3 is the length of the metering section; D is the outer diameter of the screw; Thread lead angle
[0072] The compression ratio ε is optimized using the following formula:
[0073]
[0074] Wherein, D is the outer diameter of the screw; H1 is the groove depth of the feeding section; H3 is the groove depth of the metering section;
[0075] Based on the compression ratio and the groove depth of the metering section, the following formula is used to calculate the groove depth of the feeding section:
[0076]
[0077] Among them, ε is the geometric compression ratio; D is the outer diameter of the screw; H1 is the groove depth of the feeding section; H3 is the groove depth of the metering section.
[0078] Among them, when improving the screw structure, it is necessary to optimize its thread lead angle, which is calculated using the following formula:
[0079] S = πDtanΦ;
[0080] Wherein, S is the screw pitch; D is the screw outer diameter; is the thread lead angle;
[0081] The length of the metering section L3 is calculated using the following formula:
[0082]
[0083] Where Qp is the transport rate; is the lead angle of the thread; D is the outer diameter of the screw; H3 is the groove depth of the metering section; P is the pressure on the screw; η1 is the viscosity of ETFE; L3 is the length of the metering section.
[0084] Among them, when the screw structure is improved:
[0085] The inner diameter 1 of the chamfer of the push surface is calculated using the following formula:
[0086]
[0087] Among them, R1 is the inner diameter 1 of the chamfer of the pushing surface; H3 is the groove depth of the metering section;
[0088] The inner diameter 2 of the chamfer of the push surface is calculated using the following formula:
[0089] R2 = (2-3) R1;
[0090] Among them, R2 is the inner diameter 2 of the chamfer of the pushing surface; R1 is the inner diameter 1 of the chamfer of the pushing surface;
[0091] The normal width e of the screw edge is calculated using the following formula:
[0092] e=(0.08~0.12)D;
[0093] Where, e is the normal width of the screw fin; D is the outer diameter of the screw;
[0094] The axial width b of the screw flight is calculated using the following formula:
[0095]
[0096] Among them, b is the axial width of the screw flight; e is the normal width of the screw flight; φ is the thread lead angle.
[0097] S300 , installing the screw body 102 in the double-layer metal barrel 101 , and installing a dispersing mixing element in the double-layer metal barrel 101 .
[0098] According to this specific embodiment, the part of the double-layer metal barrel 101 in contact with the screw compression section is designed as a grooved barrel and is staggered with the screw flight to form two transport grooves, a liquid phase groove and a solid phase groove.
[0099] The dispersed mixing element includes a through-groove mixing element and a convex-groove mixing element. The through-groove mixing element is installed 2D to 3D behind the melting starting point and has a length of 2D to 3D. The convex-groove mixing element is installed at the end of the screw body and has a length of 1D to 2D.
[0100] The through slot mixing element is installed at 2D to 3D after the melting starting point, and the overall length of the through slot mixing element is 2D to 3D. Before determining the position of the through slot mixing element, the melting starting point of ETFE in the compression section at different temperatures is determined experimentally. Experience has shown that the screw speed has little effect on the melting starting point, so there is no need to conduct a special experiment to determine the effect of the screw speed on the melting starting point. After determining the melting starting point, select a position 2D to 3D after the starting point to install the through slot mixing element to maximize the use of the through slot mixing element. If the mixing element is installed too far forward, the plasticization will be affected because the resin particles are not completely compacted and no physical state change occurs. After installing the through slot mixing element, continue to experiment and observe the melting state of the resin passing through the mixing element at different temperatures. Attachment Figure 4 A simplified screw structure diagram of the improved equipment is attached. Figure 5 It is the installation position of the through-groove mixing element. The overall length of the through-groove mixing element is 2D to 3D.
[0101] The present invention also provides a plasticizing device for improving the plasticizing rate of ETFE, which is applied to the method for improving the plasticizing rate of ETFE as described above.
[0102] The invention comprises a double-layer metal barrel 101 and a screw body 102 . The screw body 102 is arranged in the double-layer metal barrel 101 . The aspect ratio of the screw body 102 is 30-40, and the diameter D is 65-110 mm.
[0103] Plastic Type <![CDATA[Feeding section L1]]> <![CDATA[Compression segment L2]]> <![CDATA[Measuring section L3]]> Crystalline plastics 40%~60% (2~5D) 30%~45%
[0104] Table 1 Screw three-stage distribution length
[0105] A method and device for improving the plasticization rate of ETFE using the present embodiment is provided. The present invention installs dispersed mixing elements in the melting zone and melt conveying zone of the screw. The material passing through the melting zone enters the through groove before entering the conveying zone. The through groove is similar to a maze. The material moves in an S shape in the maze groove, so that the material is mixed more evenly. The fully melted liquid phase flows from the barrel groove into the conveying zone, and the solid-liquid mixed phase that is not fully melted continues to enter the through groove until it is completely melted and enters the conveying zone. The liquid phase entering the conveying zone is refluxed and stirred by the reverse force of the diverter plate and the extrusion, and the liquid phase is further plasticized. A convex groove mixing element is installed at the end of the screw body, and its length is 1D to 2D. The viscous fluid resin is stirred and mixed before entering the die, so that the viscous fluid resin enters the die evenly, avoiding local overheating and uneven molecular distribution. In addition, the addition of dispersed mixing elements increases the outflow rate of the resin. Under the condition of ensuring that melt fracture does not occur, the output can be increased by 30% to 40%. In this way, the technical problem in the prior art that the plasticization process of ETFE is easily affected by various factors such as the properties of raw materials, equipment structure and processing conditions, resulting in a low plasticization rate, which in turn affects the quality and performance of the final product is solved.
[0106] The invention combines the characteristics of the ETFE raw material used to improve the screw. Firstly, the conveying efficiency of the solid conveying zone is studied by using the solid conveying theory.
[0107] The formula for solid transport theory is:
[0108]
[0109] Know the depth H1 of the screw groove in the feeding section and the screw rotation angle It has a great influence on the solid conveying efficiency. In addition, the friction coefficient of the inner wall of the barrel R1, the friction coefficient of the screw surface R2 and the friction coefficient of the ETFE resin R3, the friction between these objects also affects the conveying rate. When R1, R2, and R3 are determined, and the pitch = screw diameter, θ = 17.7°. For the solid conveying angle θ, cosθ = Ksinθ + M, K acts on the coefficient of the solid plug force, and M is the collective term of the force. The relationship between K and M is as follows Figure 2 As shown, M is related to two friction factors: one is the friction factor f1 between the material and the screw; the other is the friction factor f2 between the material and the barrel. These two factors are constants when the screw material, barrel material and material type are determined.
[0110] The plasticizing method after adopting this method is:
[0111] ETFE resin is compacted after passing through the solid conveying area, and the air between the small gaps of the resin particles is also squeezed out to form a solid plug. The solid plug transitions into the melting zone, and the volume is changed by changing the screw width and screw depth. At this time, the integrity of the solid plug is destroyed and it is sheared into two or even more solid plugs. Extrusion friction occurs between the solid plugs to generate heat, and the resin begins to melt and form a molten film layer. In the transient melting theory, the moment the solid melts to form a molten film layer, it is taken away by the barrel, and the remaining solid begins to melt. The molten resin is taken away in time, and the exposed resin begins to melt, which can accelerate heat transfer, reduce resin decomposition, homogenize resin melting, and increase the resin plasticization rate. At the same time, a dispersed mixing element is installed in the melting zone, and the transient melting theory is used to guide the design of screw width and screw depth;
[0112] The resin that passes through the melting zone enters the melt conveying zone. This section uses POLYFLOW software to simulate the fluid mechanics process of the extrusion section and conducts the structural design of the screw melt conveying section. Through the simulation of geometric models and mathematical models, the boundary conditions and physical parameters are selected to conduct experimental design simulation results. The focus is on studying the influence of screw geometric parameters on the melt conveying rate, and the numerical simulation results are based on the melt conveying rate. By increasing the depth of the screw groove, the melt conveying efficiency at the extrusion metering end can be improved, and the unit consumption can be reduced. Based on this, the screw groove depth is optimized to further improve the plasticization rate.
[0113]
[0114] Table 2 Screw geometric parameters
[0115] performance performance MFR 10~20 Solid phase density ρ Liquid density <![CDATA[ρ m ]]> Solid relative heat capacity <![CDATA[C s ]]> Liquid relative heat capacity <![CDATA[C m ]]> Solid phase thermal conductivity <![CDATA[K s ]]> Liquid phase thermal conductivity <![CDATA[K m ]]> Latent heat of fusion λ Material melting point <![CDATA[T m ]]>
[0116] Table 3 Performance parameters of ethylene-tetrafluoroethylene alternating copolymer (Except MFR, other properties are replaced by letters)
[0117] What is disclosed above is only a preferred embodiment of the present invention, and it certainly cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiment and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.
Claims
1. A method for improving the plasticization rate of ETFE, characterized in that: The following steps are involved: Select ETFE raw materials with uniform molecular weight distribution, melt index of 10-20g / 10min, crystallinity of 65%-85%, and low content of foreign particles for use, and determine the physical and chemical properties of the processed materials to obtain specific processing performance parameters of the used ETFE materials; The screw structure was improved based on the solid conveying theory, transient melting theory and melt conveying theory, the screw aspect ratio was adjusted to 30-40, the screw diameter D was adjusted to 65-110 mm, the effective length L of the screw was obtained based on the screw aspect ratio, and the screw groove depth and compression ratio were optimized to obtain the screw body; The screw body is installed in a double-layer metal barrel, and a dispersing mixing element is installed in the double-layer metal barrel.
2. The method of claim 1, wherein the ETFE plasticizing rate is The molecular weight of the selected ETFE raw material is less than 1.26*10^ 6 , the impurity particle content is less than or equal to 2%.
3. The method for improving the plasticizing rate of ETFE as claimed in claim 2, wherein: The material of the screw body is tungsten carbide or high nickel alloy.
4. The method for improving the plasticizing rate of ETFE as claimed in claim 3, wherein: The specific method for optimizing the screw groove depth is: first, calculate the groove depth H3 of the metering section using the following formula, Wherein, γ is the melt shear rate; D is the outer diameter of the screw; H3 is the depth of the metering section groove; The optimal value of the metering section groove depth H3 is then calculated based on the following formula: Among them, K Q is the shape coefficient; L3 is the length of the metering section; D is the outer diameter of the screw; is the thread lead angle; The compression ratio ε is optimized using the following formula: Wherein, D is the outer diameter of the screw; H1 is the groove depth of the feeding section; H3 is the groove depth of the metering section; Based on the compression ratio and the groove depth of the metering section, the following formula is used to calculate the groove depth of the feeding section: Among them, ε is the geometric compression ratio; D is the outer diameter of the screw; H1 is the groove depth of the feeding section; H3 is the groove depth of the metering section.
5. The method for improving the plasticizing rate of ETFE as claimed in claim 4, wherein: When improving the screw structure, it is necessary to optimize its thread lead angle, which is calculated using the following formula: S = πDtanΦ; Wherein, S is the screw pitch; D is the screw outer diameter; is the thread lead angle; The length of the metering section L3 is calculated using the following formula: Where Qp is the transport rate; is the lead angle of the thread; D is the outer diameter of the screw; H3 is the groove depth of the metering section; P is the pressure on the screw; η1 is the viscosity of ETFE; L3 is the length of the metering section.
6. The method for improving the plasticization rate of ETFE as claimed in claim 5, characterized in that: When improving the screw structure: The inner diameter 1 of the chamfer of the push surface is calculated using the following formula: Among them, R1 is the inner diameter 1 of the chamfer of the pushing surface; H3 is the groove depth of the metering section; The inner diameter 2 of the chamfer of the push surface is calculated using the following formula: R2 = (2-3) R1; Among them, R2 is the inner diameter 2 of the chamfer of the pushing surface; R1 is the inner diameter 1 of the chamfer of the pushing surface; The normal width e of the screw edge is calculated using the following formula: e=(0.08~0.12)D; Where, e is the normal width of the screw fin; D is the outer diameter of the screw; The axial width b of the screw flight is calculated using the following formula: Among them, b is the axial width of the screw flight; e is the normal width of the screw flight; φ is the thread lead angle.
7. The method for improving the plasticization rate of ETFE as claimed in claim 5, characterized in that: The part of the double-layer metal barrel in contact with the compression section of the screw is designed as a grooved barrel and is staggered with the screw fins to form two transport grooves, a liquid phase groove and a solid phase groove.
8. The method for improving the plasticization rate of ETFE as claimed in claim 7, characterized in that, The dispersed mixing element includes a through-groove mixing element and a convex-groove mixing element. The through-groove mixing element is installed 2D to 3D behind the melting starting point and has a length of 2D to 3D. The convex-groove mixing element is installed at the end of the screw body and has a length of 1D to 2D.
9. A plasticizing device for improving the plasticizing rate of ETFE, applied to the method for improving the plasticizing rate of ETFE as claimed in claim 8, characterized in that: The invention comprises a double-layer metal barrel and a screw body, wherein the screw body is arranged in the double-layer metal barrel, the aspect ratio of the screw body is 30-40, and the diameter D is 65-110 mm.